A Qualitative Study Exploring How South African Female Gender-Based Violence Survivors Use Creative Expression to Communicate Their Stories Publicly - Wright, Mary-Anne Elizabeth (University of the Witwatersrand, Johannesburg, 2024)
This study investigated how South African female gender-based violence (GBV) survivors utilised creative expression to communicate their stories of GBV publicly. Within the constructivist paradigm, the study was further interested in how this public communication of GBV from the survivors themselves influenced and acted as a mode of counter-discourse in relation to the prominent discourse around GBV in South Africa. The study was done through conducting a critical narrative analysis (CNA) and visual discourse analysis (VDA) of three selected creative works, which communicated first-hand accounts of GBV, sourced from the public domain. The Pieces were selected through purposive sampling and the modes of creative expression were an artwork, a video of a performed poem, and a short story. The combination of CNA and VDA was chosen for this research as the creative works are a mixture of spoken word, written text, and other visual elements. The VDA allowed for an in-depth analysis of the visual components of the creative expressions with the hopes of providing a complete analysis within the CNA framework. Findings from this research suggest that creative works do potentially offer space for South African female GBV survivors to share their stories publicly. Through exploring social responses to the Pieces it seems that the sharing of these creative expressions further appears to have contributed to the social discourse which elicited engagement and conversation from other members of society. The creative expressions were additionally found to meet the criteria of counter-discourse. The Pieces challenge GBV dominant discourses such as victim-blaming, victimisation of survivors, and shame and stigma through relinquishing shame and blame and highlighting the strength and resilience of survivors.
A research report submitted in fulfillment of the requirements for the Master of Arts in Clinical Phsychology, In the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Creative expression; constructivist paradigm; counter-discourse; discourse; gender-based violence; public sharing; qualitative multimodal study; South African women; SDG-5: Gender equality; SDG-16: Peace, justice and strong institutions